Imatinib mesylate in first-line treatment of chronic myeloid leukemia - Ekinci, Ömer; Kızılkaya, İsmet (My University, 2019)
Objective: Chronic myeloid leukemia (CML) is a myeloproliferative disease characterized by clonal proliferation of myeloid cells. Inthis study we aimed to present our experience in patients with CML who used imatinib mesylate, a tyrosine kinase inhibitor (TKI).Aim: Sixty nine patients who were diagnosed with CML and were treated with first-generation TKI ( in the form of imatinib mesylate)as initial treatment between 2006 and 2018 were included in this retrospective study. The demographic characteristics, responserates (hematologic, cytogenetic and molecular), adverse events and overall survival (OS) rates were retrospectively analyzed.Results: There were 28 male and 41 female patients with a median age of 49.3. Hematologic, cytogenetic and molecular responsesto TKI treatment were evaluated according to the 2013 guidelines of European Leukemia Net (ELN). The complete hematologicresponse (CHR) rate at three months was 97.1%, the complete cytogenetic response (CCR) rate at 12 months was 73.4%, and themajor molecular response (MMR) at 18 months was 77.8%. The most common adverse events were cytopenia (13%), edema (10.1%),nausea/vomiting (7.2%), and musculoskeletal pain (5.8%). The mean follow-up period was 40.4 months for all CML patients, with anoverall survival (OS) rate of 84.6% during follow-up.Conclusion: As a real life data in our population, our results were consistent with those reported in the literature. Drug-relatedadverse events were minimal and tolerable. Long-term survival and disease-free survival can be achieved with proper cytogeneticand molecular monitoring under imatinib treatment and, if necessary, a change in medication.
Keywords: Tıbbi Araştırmalar Deneysel; Genel ve Dahili Tıp; Hematoloji